1999
DOI: 10.1016/s0886-3350(99)80081-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgery for cataractand glaucoma: Phacoemulsification and deep sclerectomy compared with phacoemulsification and trabeculectomy

Abstract: Deep sclerectomy combined with cataract surgery resulted in an IOP reduction similar to that with phacotrabeculectomy with the same visual outcome, but the lower complication rate makes ambulatory care easier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
3
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 16 publications
6
59
3
8
Order By: Relevance
“…9,10,20,21 Other studies reported DS and TE being equally effective. [6][7][8]11 Our results are similar to the results after trabeculectomy as reported in clinical trials comparing viscocanalostomy and TE (follow-up 1 year). 10,20 Regarding a retrospective long-term analysis comparing intensified postoperative care and conventional follow-up, the long-term complete success rate after Erbium YAG-laser-assisted deep sclerectomy is superior to the results after conventional follow-up and inferior to intensified postoperative care after trabeculectomy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…9,10,20,21 Other studies reported DS and TE being equally effective. [6][7][8]11 Our results are similar to the results after trabeculectomy as reported in clinical trials comparing viscocanalostomy and TE (follow-up 1 year). 10,20 Regarding a retrospective long-term analysis comparing intensified postoperative care and conventional follow-up, the long-term complete success rate after Erbium YAG-laser-assisted deep sclerectomy is superior to the results after conventional follow-up and inferior to intensified postoperative care after trabeculectomy.…”
Section: Discussionsupporting
confidence: 79%
“…22 The concept of reducing early postoperative complications from penetrating glaucoma surgery by performing DS was confirmed in most studies evaluating nonpenetrating procedures. 3,[5][6][7][8][9]11 In our study, the rate of complications was low. The single patient with intraoperative perforation of the TDM and subsequent iridectomy developed a flat anterior chamber and choroidal detachment.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…16 Phacoemulsification combined with DS (phaco-DS) has been shown to be as effective as phacoemulsification with trabeculectomy (phaco-trab) in lowering IOP. 14,17 In this large case series, we seek to report the outcomes of phaco-DS from a single UK centre over a 10-year period. To our knowledge, this is the largest cohort to describe this procedure with such long-term follow-up results.…”
Section: Introductionmentioning
confidence: 99%